(untitled) (International journal of artificial intelligence, 2024)
This review provides a comprehensive overview of the chemical constituents and biological effects of Hypericum perforatum L. (Hypericaceae). Extracts from Hypericum perforatum L. have been found to have a wide range of biological and pharmacological effects, including antidepressant, antibacterial, wound healing, and antimicrobial activity. The antidepressant activity of the raw material extracts may be related to the ancient use of these plants as medicinal plants. The only antidepressant principle isolated to date is vitamin B6, which is responsible for the antidepressant activity of this medicinal plant. Based on the chemical and pharmacological properties of H. perforatum, we conclude that this species has beneficial therapeutic properties and has the potential to be used as an effective adaptogenic herbal remedy.